Exploring Cognitive Engagement in EFL Descriptive Writing: A Case Study Using Mindomo-Assisted Mind Mapping - Fahmi, Kalimul; Asih Wigati, Fikri; Pujiawati, Nia (Journal of English Education and Linguistics, 2025)
This research aims to explore the process of teaching and students’ cognitive engagement in writing descriptive texts using the mind mapping technique with the Mindomo application. This research used a qualitative approach. This research was conducted in one of the public junior high schools in Karawang. The participants were nine seventh-grade students selected from one class to represent low, medium, and high levels of cognitive engagement during the descriptive writing process. Data were collected through classroom observation, interviews, and documentation. The data were analyzed by using thematic analysis. The findings indicate that the implementation of mind mapping contributed to different manifestations of students’ cognitive engagement during the writing process. Students demonstrated task management and strategic planning through visual organization of ideas, engaged in self-monitoring and revision while developing their texts from mind maps, and showed continued engagement through peer feedback and help-seeking behaviors. Students’ emotional responses were identified as contextual factors that supported persistence during the writing process. Future research could involve more participants or different text types to extend these findings.